HD-MB03 is a novel Group 3 medulloblastoma model demonstrating sensitivity to histone deacetylase inhibitor treatment - Milde, Till; Lodrini, Marco; Korshunov, Andrey; Kool, Marcel; Pfister, Stefan; Kulozik, Andreas; Witt, Olaf; Deubzer, Hedwig (Journal of neuro-oncology, 2012)
Medulloblastomas are the most common malignant brain tumors in childhood. Emerging evidence suggests that medulloblastoma comprises at least four distinct diseases (WNT, SHH, Group 3 and 4) with different biology, clinical presentation, and outcome, with especially poor prognosis in Group 3. The tight connection of biology and clinical behavior in patients emphasizes the need for subgroup-specific preclinical models in order to develop treatments tailored to each subgroup. Herein we report on the novel cell line HD-MB03, isolated from tumor material of a patient with metastasized Group 3 medulloblastoma, and preclinical testing of different histone deacetylase inhibitors (HDACis) in this model. HD-MB03 cells grow long term in vitro and form metastatic tumors in vivo upon orthotopic transplantation. HD-MB03 cells reflect the original Group 3 medulloblastoma at the histological and molecular level, showing large cell morphology, similar expression patterns for markers Ki67, p53, and glial fibrillary acidic protein (GFAP), a gene expression profile most closely matching Group 3 medulloblastomas, and persistence of typical molecular alterations, i.e., isochromosome 17q [i(17q)] and MYC amplification. Protein expression analysis of HDACs 2, 5, 8, and 9 as well as the predictive marker HR23B showed intermediate to strong expression, suggesting sensitivity to HDACis. Indeed, treatment with HDACis Helminthosporium carbonum (HC)-toxin, vorinostat, and panobinostat revealed high sensitivity to this novel drug class, as well as a radiation-sensitizing effect with significantly increased cell death upon concomitant treatment. In summary, our data indicate that HD-MB03 is a suitable preclinical model for Group 3 medulloblastoma, and HDACis could represent a therapeutic option for this subgroup.